2012
DOI: 10.1111/j.1469-8749.2011.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of flunarizine in childhood migraine: 11 years’ experience, with emphasis on its effect in hemiplegic migraine

Abstract: AIM The aim of this study was to report a single-centre experience of flunarizine in childhood migraine with focus on safety and efficacy.METHOD We conducted a retrospective observational audit of 72 individuals (40 male, 32 female; mean age 13y; age range 1y 6mo-17y) at a tertiary paediatric neurology unit between 1998 and 2009. Children were included if they had a diagnosis of migraine and at least one follow-up assessment and a minimum of 3 months' treatment with flunarizine. RESULTSOf 102 individuals ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 16 publications
(27 reference statements)
2
37
1
Order By: Relevance
“…The tolerability and side effect data are comparable with previous studies using flunarizine, in that the most common side effects reported are fatigue, weight gain and mood change []. We did not find in this patient cohort a significant association between those reporting low mood on the drug with those who had a prior history of depression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The tolerability and side effect data are comparable with previous studies using flunarizine, in that the most common side effects reported are fatigue, weight gain and mood change []. We did not find in this patient cohort a significant association between those reporting low mood on the drug with those who had a prior history of depression.…”
Section: Discussionsupporting
confidence: 86%
“…This study does suggest increased efficacy in the aura group compared with the non‐aura group. Additionally, flunarizine does seem to have a particular effectiveness in hemiplegic migraine in the paediatric population . In the majority of cases, previous migraine preventive medication had been tried before flunarizine was introduced in this patient group.…”
Section: Discussionmentioning
confidence: 96%
“…Some weaker evidence is also available for valproate,7 flunarizine,17 18 amitriptyline7 and riboflavin 7. Unfortunately, there is no good evidence for pizotifen's efficacy7 despite being a ‘licensed’ and popular treatment in the UK and it certainly seems to work well for some children and young people, in the authors' experience.…”
Section: Prophylactic Treatment For Migrainementioning
confidence: 99%
“…Many studies in adults and children have noted a high incidence of side effects with flunarizine. Incidence of significant side effects up to 21% in children have been noted, the most common of which were sedation, weight gain, and depression …”
Section: Antihypertensivesmentioning
confidence: 99%